Population and landuse based model in sewerage catchment strategy for Sungai Siput (N) - Sokalingam, Subramaniam (2007)
Growing volume of wastewater is being discharged to surface water but the treatment provided frequently is inadequate to protect the desired uses of the receiving water. With limited resources in terms of both institutional capacity and finance, government face difficult choices in optimizing their investment in wastewater system and establishing practical requirement for wastewater treatment. There is serious shortfall of adequate facilities in both rural and urban areas. This situation has a significant impact on health such as the incidence of infectious disease associated with water and sewage. Deficiencies is rapidly on the raising trend with a limited availability of resources problem associated with a small population base, low tax revenue and a sluggish economy. In urban situation the sewerage system and the extent of industrial wastewater treatment are inadequate. There may be sewerage network in place but the coverage is usually incomplete. Even where reasonable treatment facilities exist, poor maintenance and operation often result in failure to meet design effluent level. In such circumstance, management of wastewater discharge is also frequently poor, with uncontrolled discharges of untreated effluent to surface water. As a result there is high level of water pollution and it is not uncommon to have stream or water bodies, which are almost or completely anaerobic and heavily polluted with pathogens, organic and heavy metal.